Financing the Contact Investigation – TB Patients (Case Study in Mimika District, Papua, Indonesia) - Setiawan, Ery; Hafidz, Firdaus; Lestari, Trisasi (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to estimate the unit costs and budget impact of implementing a tuberculosis (TB) contact investigation program in Mimika District, Papua, Indonesia. Method: The study used a microcosting approach to calculate the unit costs of contact investigation activities. Data were collected from six community health centers (Puskesmas) over two months (July-August 2023). Cost components included human resources, medical and non-medical supplies, equipment, and transportation. Combining unit cost data with epidemiological information on TB cases in Mimika allowed for an estimate of the budget impact. Results: The average cost of a home visit for contact investigation was Rp. 53,913, with significant variations across different health centers. For example, the cost ranged from Rp. 39,214 at PKM Limau Asri to Rp. 66,494 at PKM Timika Jaya. On average, the costs were broken down into human resources (Rp. 15,946), supplies (Rp. 25,767), equipment (Rp. 2,833), and transportation (Rp. 16,000). For high-risk individuals requiring further examination, the costs varied based on the diagnostic method used. Microscopic examination cost approximately Rp. 44,482, while rapid molecular testing (TCM) was significantly higher at Rp. 541,472. Overall, the total budget impact to cover all indexed cases in Mimika District was estimated at Rp. 146,969,364. The economic analysis indicated a benefit-cost ratio of 2.62, suggesting that each rupiah invested could yield a return of 2.62 rupiah. Conclusion: Funding the TB contact investigation program in Mimika District is economically beneficial. The program's implementation would require detailed budgeting but promises substantial returns in terms of both economic and health benefits.